Small vessel disease disrupts EEG postural brain networks in 'unexplained dizziness in the elderly'. Issue 11 (November 2021) - Ibitoye, R.T.; Castro, P.; Desowska, A.; Cooke, J.; Edwards, A.E.; Guven, O.; Arshad, Q.; Murdin, L.; Kaski, D.; Bronstein, A.M.
Highlights: Unexplained dizziness in the elderly may result from cerebral small vessel disease. Dizzy elderly patients differed from controls in EEG power when standing. EEG power when standing correlated with subjective (perceived) instability. Abstract: Objective: To examine the hypothesis that small vessel disease disrupts postural networks in older adults with unexplained dizziness in the elderly (UDE). Methods: Simultaneous electroencephalography and postural sway measurements were undertaken in upright, eyes closed standing, and sitting postures (as baseline) in 19 younger adults, 33 older controls and 36 older patients with UDE. Older adults underwent magnetic resonance imaging to determine whole brain white matter hyperintensity volumes, a measure of small vessel disease. Linear regression was used to estimate the effect of instability on electroencephalographic power and connectivity. Results: Ageing increased theta and alpha desynchronisation on standing. In older controls, delta and gamma power increased, and theta and alpha power reduced with instability. Dizzy older patients had higher white matter hyperintensity volumes and more theta desynchronisation during periods of instability. White matter hyperintensity volume and delta power during periods of instability were correlated, positively in controls but negatively in dizzy older patients. Delta power correlated with subjective dizziness and instability. Conclusions: Neural resource demands of postural control increase with age, particularly in patients with UDE, driven by small vessel disease. Significance: EEG correlates of postural control saturate in older adults with UDE, offering a neuro-physiological basis to this common syndrome.